The Methodology of Research Institutions in Developing Maqāṣid Thought: The Contributions of the International Institute of Islamic Thought (IIIT) in Renewing Maqāṣid al-Sharīʿah through the journal Islāmiyyat al-Maʿrifah - Nouassa, Youcef (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2020)
The International Institute of Islamic Thought (IIIT) has had a significant interest in maqāṣiḍ al-Sharīʿah (the objectives of Shariʿah), researching its issues and attempting to practically implement and renew maqāṣid thought. This has been evident in IIIT’s general publications and in the research it has published through its journal Islāmiyyat al-Maʿrifah (now published under the title Al-Fikr al-Islāmī al-Muʿāṣir). Though IIIT’s publications have generally received critical and analytical attention, the same cannot be said for the research published in its journal. It therefore behooves us to critically and analytically examine the intellectual and epistemological makeup of this research and to offer an integrative structural reading of it in order to form a general conception of these efforts to renew maqāṣid al-Sharīʿah and to highlight the invaluable strengths found therein, while redressing areas where there are flaws; then reviewing all of this to highlight the value and importance of this research.